2015
DOI: 10.11648/j.ijmi.20150301.11
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of Hydronephrosis and Determination of the Main Causes among Adults

Abstract: Abstract:Background: hydronephrosis is one of the most common complication of renal obstructive diseases, if left untreated, it may cause severe complications which may lead to acute and chronic renal failure. Objectives: to assess and classify hydronephrosis and determine the causes using ultrasound. Materials and methods: It is a prospective study, the study population composed of 53 female and 47 male who were suspected with renal diseases and referred to the ultrasound department for investigation. Data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…The severity of hydronephrosis was shown to be correlated with the presence of detected stones. This was consistent with a recent research by Suzan et al who found that renal stones were the cause of hydronephrosis in 54% of adult patients 17 58.4% of the patients in this research were male, whereas 41.5% were female. Renal calculi were more common in men as they were in women, which is consistent with findings from prior research by Nuraj P et al 18 The distribution of hydronephrosis grades in this research is comparable to that reported by Nuraj P et al 6 who found a prevalence of 48% for grade 2, 22.8% for grade 1, 16.2% for grade 3, and 12.5% for grade 4, and that by Alshoabi 8 as well.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The severity of hydronephrosis was shown to be correlated with the presence of detected stones. This was consistent with a recent research by Suzan et al who found that renal stones were the cause of hydronephrosis in 54% of adult patients 17 58.4% of the patients in this research were male, whereas 41.5% were female. Renal calculi were more common in men as they were in women, which is consistent with findings from prior research by Nuraj P et al 18 The distribution of hydronephrosis grades in this research is comparable to that reported by Nuraj P et al 6 who found a prevalence of 48% for grade 2, 22.8% for grade 1, 16.2% for grade 3, and 12.5% for grade 4, and that by Alshoabi 8 as well.…”
Section: Discussionsupporting
confidence: 93%
“…21 Another research by Suzan Omer Abdelmaboud et al found that 53% of Khartoum residents with hydronephrosis had only mild symptoms, whereas 30% had moderate symptoms, and 13% had severe symptoms, based on ultrasound evaluations, and therefore it may be prudent to screen all patients with even mild symptoms for the presence of renal and ureteric stones. 17 The majority of patients were from the very low and low income status, and a study showed that patients with lower education levels and from regions of lower mean income were found to be more likely to present to our tertiary care center with a greater stone burden, and the majority of patients in our study had grade 3 hydronephrosis. 22 However, in certain situations, a more thorough diagnosis may need the use of additional imaging modalities, such as CT or MRI.…”
Section: Discussionmentioning
confidence: 54%
“…These results are consistent with a previous study by Suzan et al (2015), who reported that kidney and ureteric stones were the cause of hydronephrosis in 54% of adult patients. 8 The gender distribution of the patients in the sample of this study was 67.14% males vs. 32.86% females. This result is compatible with previous studies by Hall (2009) and Nuraj P et al (2017), who reported that renal calculi in males were nearly twice as it was in females.…”
Section: Discussionmentioning
confidence: 71%
“…Comparative analyses with prior studies reveal interesting parallels and deviations in the detection rates and clinical presentations of HDN. For instance, Suzan et al categorized HDN sonographically into three types, identifying mild HDN as the most common, occurring in approximately 53% of cases, followed by moderate HDN in 30%, severe HDN in 13%, and extreme HDN in a mere 4% of patients (14). Similarly, Jacob et al linked the grade of HDN observed on ultrasonography with the size of kidney stones, noting that a significant majority of patients with mild HDN harbored smaller urethral stones measuring under 5mm (15).…”
Section: Discussionmentioning
confidence: 99%